Factors Supporting the Implementation of Green Accounting with Profitability as an Intervening Variable - Puspita, Apriliana Sindy; Purbasari, Heppy (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The purpose of this study was to examine the influence of environmental costs, and firm value on green accounting, mediated by profitability. The research method used is a quantitative research method. The population in this study is all companies listed on the Indonesia Stock Exchange (IDX) except in the financial sector. The sampling technique is a purposive sampling technique based on certain criteria so that a sample of 182 data is obtained. The type of data used is secondary data and the analysis technique used is multiple linear regression analysis with the Sobel Test test tool. The results of the study show that environmental costs and firm value affect profitability, while environmental costs and profitability have no affect on green accounting but firm value affects green accounting. The results of the study also show that profitability cannot mediate the influence of environmental costs and firm value on green accounting.